IJMA` DAN QIYAS (Analisis Komparatif dalam Ushul Fiqh) - Iksan Abdiman; Rifki Januari; Agustiawan Agustiawan; Farhan Anugrah Qodafi (CV. ITTC INDONESIA, 2025)
This article discusses the concepts of Ijma' (consensus of scholars) and Qiyas (analogy) as two important methods in Usul Fiqh (principles of Islamic law). Ijma' is the consensus of mujtahids (jurists) during the period following the death of the Prophet Muhammad. Qiyas is a method of establishing new laws based on the similarity of 'illat (legal reasoning) with cases already stipulated in the Qur'an or Sunnah. This article aims to analyze the definitions, divisions, validity of the evidence, and functions of Ijma' and Qiyas according to various scholars' perspectives.